BIOLOGÍA REPRODUCTIVA DE «BOQUICHICO», Prochilodus nigricans, EN LA AMAZONÍA PERUANA - MONTREUIL-FRIAS, Víctor Hugo (2001)
Reproduction of «boquichico» Prochilodus nigricans, at the Peruvian Amazon takes place from December to March, coinciding with the period of water rising of the Amazon River, not showing a clear relationship with the increment of local raining. This species reaches its average size of maturity at a fork length of 24,3 cm., in females, and 23,4 cm., in males.